STRESS, ANXIETY, AND DEPRESSION IN STOMATITIS PATHOGENESIS: A SYSTEMATIC REVIEW - Cahyono, Bagus Dwi; Huda, Nurul; Aristawati, Evy; Aditya, Ronal Surya; Rahmawati, Apriana; Kusuma, Erik; Nasriati, Ririn (Universitas Airlangga, 2025)
Introduction: Recurrent Aphthous Stomatitis (RAS) is a chronic inflammatory condition characterized by painful ulcers on the oral mucosa. Emerging evidence indicates that psychological factors, such as stress, anxiety, and depression, may play a role in its development. This review aims to examine the influence of these mental health factors on the onset and progression of RAS based on recent scientific literature. Methods: he exact mechanisms through which psychological stressors contribute to RAS remain poorly understood. To address this, a systematic review was conducted following PRISMA guidelines to consolidate current research findings. A thorough search was performed across PubMed, the Cochrane Library, and Google Scholar to identify original studies published within the past decade. The search terms used were: (